2020
DOI: 10.1002/ajmg.a.61608
|View full text |Cite
|
Sign up to set email alerts
|

Aortic arch geometry predicts outcome in patients with Loeys–Dietz syndrome independent of the causative gene

Abstract: This study aimed to investigate the potential association between imaging features and cardiovascular outcomes in patients with Loeys-Dietz syndrome (LDS). We performed a retrospective cohort study of 36 patients with LDS and described cardiovascular events and imaging data. We observed different clinical courses in patients with LDS, irrespective of the causative gene. Angular or elongated aortic arch geometry correlated with aortic dissection (R = .39, p = .02), occurrence of the first cardiovascular event b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…There were few reported individual cases of LDS Type 3 (n = 39), with only a quarter P. Gouda et al considered high quality, leading to low quality prevalence estimates from the summation of these studies (Table 2). Amongst high-quality cohort studies (14,15,(17)(18)(19), that ranged from 9 to 45 individuals (Supplementary Table 5), we observe that this cohort is uniquely characterised by the presence of early onset osteoarthritis (41-96%) and osteochondritis dissecans (56%), which is frequently the symptoms that leads them to present for medical consultation (Table 3). In addition, they demonstrated a high frequency of aortic aneurysms (50-79%), and arterial tortuosity of the cerebral arteries (50% Variables with a frequency of <10 across all LDS types removed including: superior mesenteric artery aneurysm, left ventricular hypertrophy, atrial fibrillation, cardiac arrest, protrusio acetabulae, osteoporosis, osteoarthritis, intervertebral disc degeneration, spondyloses, spondylolisthesis, dental malocclusion, ectopia lentis, atrophic scars, Chiari malformation, hydrocephalus, uterine/bladder/bowel prolapse, varices, food allergies, eczema, eosinophilic esophagitis/gastritis, inflammatory bowel disease.…”
Section: Lds Typementioning
confidence: 99%
See 2 more Smart Citations
“…There were few reported individual cases of LDS Type 3 (n = 39), with only a quarter P. Gouda et al considered high quality, leading to low quality prevalence estimates from the summation of these studies (Table 2). Amongst high-quality cohort studies (14,15,(17)(18)(19), that ranged from 9 to 45 individuals (Supplementary Table 5), we observe that this cohort is uniquely characterised by the presence of early onset osteoarthritis (41-96%) and osteochondritis dissecans (56%), which is frequently the symptoms that leads them to present for medical consultation (Table 3). In addition, they demonstrated a high frequency of aortic aneurysms (50-79%), and arterial tortuosity of the cerebral arteries (50% Variables with a frequency of <10 across all LDS types removed including: superior mesenteric artery aneurysm, left ventricular hypertrophy, atrial fibrillation, cardiac arrest, protrusio acetabulae, osteoporosis, osteoarthritis, intervertebral disc degeneration, spondyloses, spondylolisthesis, dental malocclusion, ectopia lentis, atrophic scars, Chiari malformation, hydrocephalus, uterine/bladder/bowel prolapse, varices, food allergies, eczema, eosinophilic esophagitis/gastritis, inflammatory bowel disease.…”
Section: Lds Typementioning
confidence: 99%
“…In studies with serial follow-up, rates of aortic root dilation ranged from 0.11-0.67 cm/year (13,20,29), with children with LDS type 2 demonstrating the greatest progression of aortic root dilation compared to LDS type 1 and 4 (30). Several studies have also identified a correlation between the presence of craniofacial features (13,14), carotid artery tortuosity (31), vertebral artery tortuosity (32), aortic arch geometry (33), aortic stiffness (34), and mitral annular disjunction (35) with increased aortic risk. Aortic root dilation in children should lead to the suspicion of connective tissues disorders, including LDS.…”
Section: Cardiovascular Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial tortuosity is likely a general (albeit easily standardized and quantified) surrogate of the overall clinical severity that is imposed by the specific underlying disease allele, as opposed to a direct contributor to vascular events. Other imaging techniques such as aortic arch geometry, aortic tortuosity index, carotid tortuosity indices, and the chalice sign have been proposed as either predictors of disease severity or diagnostics markers in LDS (Benson & Brinjikji, 2020;Chu et al, 2018;Mariucci et al, 2020;Morris et al, 2011). 4D-Flow cardiovascular magnetic resonance angiography allows for assessment of volumetric flow quantification, wall shear force, pulse wave velocity, aortic stiffness, and pressure gradients, providing the potential to improve our ability to interpret altered hemodynamics in the context of disease progression and management (Di Giuseppe et al, 2021;Markl et al, 2012).…”
Section: Looking Forward: Imagingmentioning
confidence: 99%
“…Arterial tortuosity is likely a general (albeit easily standardized and quantified) surrogate of the overall clinical severity that is imposed by the specific underlying disease allele, as opposed to a direct contributor to vascular events. Other imaging techniques such as aortic arch geometry, aortic tortuosity index, carotid tortuosity indices, and the chalice sign have been proposed as either predictors of disease severity or diagnostics markers in LDS (Benson & Brinjikji, 2020; Chu et al, 2018; Mariucci et al, 2020; Morris et al, 2011).…”
Section: Looking Forward: Imagingmentioning
confidence: 99%